2018
DOI: 10.1542/peds.2017-4058
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Neuroimaging and School-Age Cognitive Outcomes

Abstract: Background and Objectives: Children born extremely preterm (EPT) are at risk for cognitive difficulties and disability. The relative prognostic value of neonatal brain MRI and cranial US (CUS) for school-age outcomes remains unclear. Our objectives were to relate near-term conventional brain MRI and early and late CUS to cognitive impairment and disability at 6–7 years among children born EPT, and assess their prognostic value. Methods: A prospective study of adverse early and late CUS and near-term conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 42 publications
2
46
0
1
Order By: Relevance
“…Model fit values indicated that the developmental pathways included in this study accurately reflect the true neurodevelopmental mechanisms in the two populations studied. Thus, our results confirm previous evidence suggesting that repeated early head circumference measurements are a valuable and easy screening tool for long-term neurocognitive risk assessment after preterm birth, in particular in light of recent findings refuting the diagnostic benefits of routine MRI on preterm infants (Edwards et al, 2018; Hintz et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Model fit values indicated that the developmental pathways included in this study accurately reflect the true neurodevelopmental mechanisms in the two populations studied. Thus, our results confirm previous evidence suggesting that repeated early head circumference measurements are a valuable and easy screening tool for long-term neurocognitive risk assessment after preterm birth, in particular in light of recent findings refuting the diagnostic benefits of routine MRI on preterm infants (Edwards et al, 2018; Hintz et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…After Linking brain-age trajectories with neurodevelopmental outcome. Figure 3 shows the overall test performance on 2 after training on the entirety of 1  . The trajectory summary metrics are shown for all values of N f , and compared between the normal and abnormal outcome groups.…”
Section: Resultsmentioning
confidence: 99%
“…Two separate cohorts of patients were recruited, resulting in two separate EEG datasets referred to as 1  and 2  in this study, respectively. 1  consisted of 89 EEG recordings from 26 patients with PMA range 27.3-42.0 weeks (median recording duration (IQR): 4 h 23 m (3 h 53 m-5 h 46 m), median number of recordings per patient: 3 (3-4)) and were recruited in the period February 2013 -September 2014. These were preselected based on a normal neurodevelopmental outcome at nine and 24 months of corrected age, clinically defined according to Pillay et al 32 and Dereymaeker et al 33 and based on the Bayley Scores of Infant mental and motor Development II (BSID-II).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Each of these neonatal morbidities is predictive of adverse neurodevelopmental impairment. [3][4][5][6][7][8][9][10][11] To the extent that neonatal morbidities lie on a causal pathway connecting extremely preterm birth to adverse child health and neurodevelopmental outcomes, interventions that target antecedents of BPD, NEC, sepsis, severe brain injury, and ROP have the potential for increasing the likelihood that an extremely preterm birth will remain free from chronic health or developmental problems.…”
Section: Introductionmentioning
confidence: 99%